2010
DOI: 10.1038/jcbfm.2009.283
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of PAR4 Attenuates Cerebral Ischemia/Reperfusion Injury in Mice

Abstract: Stroke is the third leading cause of death in the USA. Antithrombotic therapy targeting platelet activation is one of the treatments for ischemic stroke. Here we investigate the role of one of the thrombin receptors, protease-activated receptor 4 (PAR4), in a mouse transient middle cerebral artery occlusion (MCAO) model. After a 60 min MCAO and 23 h reperfusion, leukocyte and platelet rolling and adhesion on cerebral venules, blood-brain barrier (BBB) permeability, and cerebral edema were compared in PAR4-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 38 publications
2
27
1
Order By: Relevance
“…PAR-2 has been found to regulate mast cells infiltration and Tcell activation and the Th1/inflammatory response in experimental periodontitis of mice [31], and activation of PAR-2 results in mast cell degranulation [32]. PAR-4 has been reported to participate platelet activation and microvascular inflammation in cerebral ischemia/ reperfusion (I/R) injury [33], and to leads to proinflammatory changes in the knee joint [34]. These findings implicate the importance of PARs in promoting inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…PAR-2 has been found to regulate mast cells infiltration and Tcell activation and the Th1/inflammatory response in experimental periodontitis of mice [31], and activation of PAR-2 results in mast cell degranulation [32]. PAR-4 has been reported to participate platelet activation and microvascular inflammation in cerebral ischemia/ reperfusion (I/R) injury [33], and to leads to proinflammatory changes in the knee joint [34]. These findings implicate the importance of PARs in promoting inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…While these findings demonstrate a major role for platelet PAR4 in promoting leukocyte recruitment in our endothelial injury model, PARs' contributions to thromboinflammatory responses such as ischaemia-reperfusion injury remain controversial. Some studies have suggested that PAR activation is critical for ischaemia-reperfusion-induced organ injury 52 ; however, others failed to identify a role of PARs in linking coagulation with inflammation 53 . Such discordant conclusions may reflect the variable influence of platelet activation on thromboinflammatory reactions in different experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…3 Consistent with this, platelet depletion or inhibition of platelet activation improves microvascular perfusion and reduces tissue inflammation and injury. [4][5][6][7] Experimental and clinical evidence has demonstrated that thrombi are highly efficient at recruiting leukocytes from flowing blood 8 with the extent of the thromboinflammatory response correlating with the degree of organ injury and clinical outcome. 9 Despite its clinical importance, there is limited understanding of the mechanisms by which microvascular thrombi guide leukocytes to sites of vascular injury.…”
Section: Introductionmentioning
confidence: 99%